Edukasi Budi Daya Sayuran Sehat dengan Teknik Hidroponik Berbasis Eco-friendly di Kampung Nelayan Cilallang, Sulawesi Barat - Mufti Hatur Rahmah; Suyono Suyono; Suparman Suparman; Nurmadina Nurmadina (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Cilallang Fisherman's Village is a densely populated settlement because it is included in the Majene city area so that residents are constrained by the limited availability of land for farming. This Fisherman's Village is also a stunting locus that requires special attention in fulfilling nutritional intake for the children of local fishermen. Another condition that also occurs in this village was the high rate of waste disposal, both in the form of organic waste and inorganic waste. Therefore, this mentoring program aimed to provide education on how to grow healthy vegetables using the hydroponic technique, which did not require a large area of land and the planting media could use plastic waste from residents so that it was eco-friendly. The activity was carried out in several stages, namely: the preparation stage, the training stage, and the monitoring and evaluation stage. The results of the analysis of activity questionnaire data consisting of 31 respondents were 73.95% strongly agree (SS) and 23.56% agree (S) obtained the benefits of eco-friendly hydroponic vegetable cultivation education.